The Level of Social Competence among Kindergarten Students According to Montessori Curriculum from their Teachers Viewpoint in Qatar - Al-Ahmad, Somayyah Nasri; Abu Sneineh, Odeh Abdel Jawad (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify The Level of Social Competence among Kindergarten Students According to Montessori Curriculum from their Teacher’s viewpoint in Qatar. The descriptive approach was used, a scale of social competence was developed, and its psychometric properties were verified. The study sample consisted of kindergarten students who follow the Montessori curriculum and who follow the normal curriculum numbering (109) students. They were selected by purposive sample, for the second semester of the year (2020/2021). The results showed that the level of social competence among kindergarten students according to the Montessori curriculum came at a high level. As showed, there were statistically significant differences in the level of social competence among kindergarten students according to the curriculum variable and in favor of the Montessori curriculum. As there were statistically significant differences in the level of social competence of children in the Montessori curriculum according to the variable of gender in favor of females, And according to the variable of the mother’s profession in favor of the working mother, And to the absence of statistically significant differences according to the variable of mother’s educational attainment. In the normal curriculum, there were no statistically significant differences according to the variables (gender, mother’s profession, and mother’s educational attainment. The study recommended conducting similar studies in Jordan and applying them to Montessori kindergartens and comparing them with the normal kindergartens.
Keywords: Social competence; The Montessori curriculum; Kindergarten